Semiotics and market research (the other half of the equation) - Valentine, Virginia (Henry Stewart Talks, 2008)
Explaining semiotics; the theory of meaning-production, Decoding the unconscious communications of brands, Tracking cultural paradigm shifts and spotting future cultural trends, Rational and emotional languages, Slotting semiotics into the market research process, When, where and how to make the most of its unique contribution